2015
DOI: 10.4103/0019-5049.171567
|View full text |Cite
|
Sign up to set email alerts
|

Current views and practice of faculty members and consultants regarding ′Publications in India′: A cross-sectional study

Abstract: Background and Aims:There is an increasing enthusiasm and pressure to submit scientific articles to journals for publication due to official policies. This has led to increased stress on authors and editors and in issues like plagiarism. We planned a cross-sectional study with an aim to explore the current publication related views and practice of faculty members and consultants.Methods:We conducted a questionnaire based prospective survey with 22 questions divided into parts. Print and electronic versions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[5] In a survey on current publication-related views and practice of faculty members and consultants, it was found that the publication rule had become a burden for 46% respondents; 27% respondents felt that publications are a mandatory stress, 57.3% felt that the mandatory number of publications induces unhealthy competitions and 56.1% felt that the rule of mandatory publications exerts undue stress on editors of national and indexed journals. [8] This survey though portrays interesting opinions of Indian anaesthesiologists on some aspects of publications has a low response rate; nevertheless, there are currently no other survey results published in India on this topic. Often, the articles written by Indian researchers are deficient in grammar and adequate references.…”
Section: Stress On Medical College Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In a survey on current publication-related views and practice of faculty members and consultants, it was found that the publication rule had become a burden for 46% respondents; 27% respondents felt that publications are a mandatory stress, 57.3% felt that the mandatory number of publications induces unhealthy competitions and 56.1% felt that the rule of mandatory publications exerts undue stress on editors of national and indexed journals. [8] This survey though portrays interesting opinions of Indian anaesthesiologists on some aspects of publications has a low response rate; nevertheless, there are currently no other survey results published in India on this topic. Often, the articles written by Indian researchers are deficient in grammar and adequate references.…”
Section: Stress On Medical College Teachersmentioning
confidence: 99%
“…[17] As mentioned by an author and also found in a survey, the MCI rule of mandatory publications has encouraged plagiarism. [58]…”
Section: Promotion Of Scientific Misconductmentioning
confidence: 99%
“…Today, the real scientific world is at risk of getting overshadowed and inundated under the cloud of 'pseudo science'. [3][4][5] This editorial is aimed at increasing awareness for the readers of this journal about the magnitude of the crisis in the field of scholarly publications, by highlighting various pertinent issues with emphasis on a relatively obscure aspect of publishing -bibliometric indices and our preoccupation with such. While the well known forms of publication misconduct continue unabated, such as authorship issues, conflicts of interest, plagiarism in its various forms, research fraud, salami slicing, it is of concern that the entire scholarly publication process should not get hijacked.…”
mentioning
confidence: 99%
“…While the well known forms of publication misconduct continue unabated, such as authorship issues, conflicts of interest, plagiarism in its various forms, research fraud, salami slicing, it is of concern that the entire scholarly publication process should not get hijacked. [2][3][4][5] Today, knowingly or unknowingly, a significant proportion of stakeholders in the field of scientific publications ranging from the authors, reviewers, editors and even the publishers often indulge in blatant violation of publication ethics in its various forms. Individual author misconduct has been known since a while now.…”
mentioning
confidence: 99%
See 1 more Smart Citation